Safety profile, antiviral capacity, and liver protection of a nasal therapeutic vaccine in patients with chronic hepatitis B: Five-year-follow-up outcomes after the end of treatment - Al Mahtab, Mamun; Akbar, Sheikh Mohammad Fazle; Aguilar, Julio Cesar; Yoshida, Osamu; Khan, Sakirul; Gerardo, Guillen Nieto; Hiasa, Yoichi (Frontiers in Medicine, 2023)
Introduction There is a pressing need to develop novel drugs for treating patients with chronic hepatitis B (CHB), as commercially available antiviral drugs are endowed with safety and efficacy concerns. Methods A phase III clinical trial was conducted with a therapeutic vaccine containing two antigens of the hepatitis B virus (HBV; named NASVAC) in 78 patients with CHB expressing both HBV DNA and elevated levels of alanine aminotransferase (ALT) in the blood. Five years after the end of treatment (EOT), 60 NASVAC-recipient patients were enrolled in this long-term follow-up study to evaluate the safety, antiviral potential, and liver-protective capacity of NASVAC. Results NASVAC exhibited an excellent safety profile 5 years after EOT. The levels of HBV DNA in the sera were reduced in 55 of the 60 patients, and 45 of them were negative for HBV DNA in the sera. ALT levels were also normalized in 40 of the 60 patients 5 years after EOT. None of the patients receiving NASVAC developed liver cirrhosis or cancer. Discussion The present study is the first to exhibit long-term follow-up data of a finite immune therapy for CHB that is safe and endowed with potent antiviral and liver-protecting capacities.